Managing Projects for Value - Goodpasture, John (Berrett-Koehler Publishers, 2001)
With a clear focus on how business objectives determine project value, this book explains how to use an "investment-based" perspective to integrate finance, risk management and strategic planning. You'll develop workflows that overcome constraints of time, cost and scheduling as you benefit from new tools that relate processes directly to business goals: the project balance sheet and the time-centric earned value system. In addition, a new goal decomposition methodology gives you the best chance of getting projects started - and getting them accomplished successfully